EARLY DIAGNOSIS AND TREATMENT IN PATIENT WITH A PRIMARY CILIARY DYSKINESIA (KARTAGENER SYNDROME): CASE REPORT - I. V. Rybakova; I. V. Koroleva; A. V. Khizhniak; O. V. Sidorovich; S. Iu. Elizarova (Архивъ внутренней медицины, 2018)
Primary ciliar dyskinesia is а rare orphan disease known for its multiple and variable symptoms caused by the marked genetic heterogenity beyond. As per the abundant symptoms in pediatric patients, a frequent inflammatory diseases of both upper and lower respiratory tract segments are the key points. A Sieberth-Kartagener Syndrome is a classical form of the primary ciliary dyskinesia covered such symptoms as the reversal placement of internal organs, chronic bronchoectases, nasal cavity hypoplasia and/or sinusitis. According to some foreign research, the age mediana value estimated in Eastern and Western European countries for a “Primary Ciliary Dyskinesia” diagnosis is equal to about 5 years. A lack of early diagnosis is nothing but a direct consequence of the poor level of awareness, so common for a primary health care system. This itself leads to increased rates of patients disability. This report deals with clinical peculiarities, diagnostics and treatment details observed and administered in a primary ciliary dyskinesia (Kartagener Syndrome) patient. Noteworthy, both mother’s tough obstetric-gynecological profile and a harsh course of this particular pregnancy were indeed taken into account. Up until 11 months, this patient was subjected to a non-clinical treatment on numerous respiratory infection occasions. A “Kartagener Syndrome” diagnosis was estimated in our clinic on the basis of laboratory and instrumental tests data. Thus, the latter prove a complete reversal of internal organs placement. Further, this diagnosis was re-confirmed by histomorphological patterns revealed in the nasal epithelial biopsy study. A difficulty to come up with the Kartagener Syndrome diagnosis at the pre-hospital treatment stage is in a focus of this specific case report. Noteworthy, we have succeed with the early diagnosis of Kartagener Syndrome and then with a following efficient therapy conducted in our clinic.